Religious education on the oppressed in Shiites- Rooting and means - Al- Ashwal, Aziza Ali (Journal of Islamic Sciences, 2020)
One of the basic tenets of the Shiite ideology is the decimal: The doctrine of injustice, It is said that the house of the Prophet (peace and blessings of Allaah be upon him) has been subjected to injustice by their enemies (Ahl al- Sunnah) And that this injustice continues from the time of prophecy to the present day, and will not end until the departure of their Mahdi expected, and the research has presented this idea and dimensions of the path descriptive analytical approach, and how the Shiites are rooting this idea through many novels, and are keen to raise their children and their followers to feel And the frequent activity of Husayniyat to deepen this feeling and apply the principle of adaptation in education, as well as the principle of continuous repetition, They are the two imams The evil of them, and they have succeeded in achieving educational goals to a large extent, with the presence of negligence and failure when many Sunni communities in instilling the true faith, values ​​and principles straight in the hearts of their children, and not to benefit from the means of religious events in the achievement of Islamic education goals in Complies with religious regulations.
Keywords: Shiites; Oppressed; Imams; Hussein; Education; Doctrine